PROSPECTS FOR THE USE OF WASTE OILS AS ALTERNATIVE FUEL IN TECHNOLOGICAL PROCESSES OF MANUFACTURING OF CASTINGS AND FOUNDRY MOLDS - A. S. Panasugin; N. P. Masherova; D. P. Michalap; S. P. Zadrutsky (Литьë и металлургия, 2015)
Quantitative and qualitative composition of the gas emission has been investigated. Quantity of CO, СО2, NOx, О2, paraffin hydrocarbons and benzene derivatives in the reaction zone depending on the duration of the process and temperature 400–800 ºС has been determined. The list of organizations utilizing waste oils as alternative fuel is presented